THE URGENCY OF LEGAL PROTECTION AGAINST THE IMPLEMENTATION OF ELECTRONIC INFORMATION TECHNOLOGY-BASED MEDICAL RECORDS IN REGULATION OF THE MINISTER OF HEALTH OF THE REPUBLIC OF INDONESIA NUMBER 269 OF 2008 - Hutabarat, Dany Try Hutama; Zebua, Rusti; Sitorus, Rini Andriani; Subakti, Febby Andriana; Ramadhani, Hikmah; Mangunsong, Juliana; Nduru, Firma; Alfah, Gusthi Sulistio; Pasaribu, Julio Calvin Dheo; Malau, Rado Maruli; Anhar, Ibnu; Sahdan, Patria (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
Indonesia is a country that until now has not have a single law laws specifically regulating the protection of personal data. Lately there have been many cases in the community regarding the misuse of personal data. Especially with the increasingly easy public access to the internet so that the misuse of personal data through electronic media will spread quickly. In the field of health services, the patient's personal data cannot be separated from the possibility of abuse. It would be even more dangerous if the personal data is a trace of the patient's medical record which is indeed highly confidential. The use of Information and Communication Technology (ICT) in health services aims to improve access, efficiency, effectiveness, and quality of medical processes that involve medical service organizations in hospitals, clinics, health centers, medical practitioners both doctors and therapists, laboratories, pharmacies, insurance also involving patients as consumers. However, in the process of service using the E-health program, it will collect a number of consumer personal data which is sensitive personal data and lead to new legal issues, namely the extent to which the health service provider can protect patient personal data can be accessed, disseminated more easily through the progress of ICT. So far, the existing regulations have not provided maximum protection for patient personal data because the arrangements are still sectoral and are scattered in several laws and regulations.